Homologous recognition promoted by RecA protein via non-Watson-Crick bonds between identical DNA strands. - Rao, B J (1993)
The RecA protein of Escherichia coli forms a nucleoprotein filament that promotes homologous recognition and subsequent strand exchange between a single strand and duplex DNA via a three-stranded intermediate. Recognition of homology within three-stranded nucleoprotein complexes, which is probably central to genetic recombination, is not well understood as compared with the mutual recognition of complementary single strands by Watson-Crick base pairing. Using oligonucleotides, we examined the determinants of homologous recognition within RecA nucleoprotein filaments. Filaments that contained a single strand of DNA recognized homology not only in a complementary oligonucleotide but also in an identical oligonucleotide, whether their respective sugar-phosphate backbones were antiparallel or parallel, and a filament that contained duplex DNA showed the same polymorphic versatility in the recognition of homology. Recognition of self by a filament that contains a single strand reveals that RecA filaments can recognize homology via non-Watson-Crick hydrogen bonds. Recognition of multiple forms of the same sequence by duplex DNA in the filament shows that it primarily senses base-sequence homology, and suggests that recognition can be accomplished prior to the establishment of new Watson-Crick base pairs in heteroduplex products. However, unlike the initial recognition of homology, strand exchange is stereospecific, requiring the proper antiparallel orientation of complementary strands.